DISTRIBUSI FREKUENSI LITERASI DIGITAL REMAJA DI KALANGAN SISWA MENENGAH PERTAMA DI KECAMATAN PAMIJAHAN - Mardiatama, Welinda; Muslikhah , Febri Palupi; Ernawati, Erna; Kuntoro, Diadji (JURNAL SAHID DA'WATII, 2024)
Advances in internet technology have made it easier for people to communicate and access information, making digital literacy an important skill in the digital era. Digital literacy involves technical skills to access media, critical understanding to analyze content, and communicative skills to participate and create through social media. This research aims to analyze the frequency distribution of digital literacy among junior high school students in Pamijahan District. Data shows that the majority of respondents have a high level of digital literacy (40.1%), while the rest range from moderate to very low. Even though students are generally able to use social media actively, their understanding of risks such as the spread of fake news and cybercrime still needs to be improved. Research has shown that having good digital literacy helps students to sort information better, but improvements in digital ethics and safety are still needed to minimize the negative impacts of digital media use among teenagers.